Pleading the Blood: Towards a Pentecostal Theology of Eucharistic Sacrifice - Black, Jonathan (Journal of pentecostal theology, 2022)
Although Pentecostals have given much attention to the Breaking of Bread, they have not generally considered it from the perspective of eucharistic sacrifice. Yet, from the earliest days of the history of the church, and with remarkable consistency across the ancient divisions of the church, the Eucharist has been recognised as a sacrifice. This article draws on the significant British Pentecostal concept of pleading the blood, along with the proto-Pentecostal Catholic Apostolic Church, and D.P. Williams’ understanding of the heavenly priesthood of Christ, in conversation with the wider church, to work towards a Pentecostal theology of eucharistic sacrifice, which would also have wider ecumenical potential for Protestant understandings of the Lord’s Supper.